Phase formation between Ni thin films and GaAs substrate. (December 2017) - Rabhi, S.; Perrin-Pellegrino, C.; Zhiou, S.; Benoudia, M.C.; Texier, M.; Hoummada, K.
Abstract: In situ X-Ray Diffraction, X-Ray Reflectivity and High Resolution Transmission Electron Microscopy were used to investigate the sequence and the texture of phase formation during the solid-state reaction of Ni thin film with GaAs substrate. These results show the formation of a unique Ni3 GaAs crystalline phase at 200 °C that remains stable until 400 °C. The epitaxial relationships between this phase and the GaAs substrate were also evidenced. The formation of this unique phase, along with the variation of its lattice parameters when Ni is totally consumed, can be explained by local thermodynamic equilibrium and kinetics arguments. Graphical abstract: